Dizziness, Physical Exercise, Falls, and Depression in Adults and the Elderly - Teixeira,Adriane Ribeiro (2016)
Abstract Introduction Dizziness is a symptom that can lead to falls, which, in turn, undermine oné s independence and autonomy, leading to several comorbidities. The practice of physical exercise, however, can help prevent falls. Objective The objective of this study is to confirm the association between physical exercise, dizziness, probability of falling, and depressive symptoms in a group of middleaged adults and seniors. Methods The authors evaluated subjects based on history, the Geriatric Depression Scale, and functional reach test. Results The sample consisted of 90 individuals with a mean age of 69.3 6.8 years. The authors found that 37.8% had been practicing exercise, 33.7% had depressive symptoms, and their probability of falling was above average in the functional reach test. Conclusion The results of this study indicated an association between dizziness, exercise practice and depressive symptoms, indicating that physical activity is a beneficial factor for the aging population.